2012
DOI: 10.1053/j.gastro.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infects the Endothelial Cells of the Blood-Brain Barrier

Abstract: BACKGROUND & AIMS Hepatitis C virus (HCV) infection leads to progressive liver disease and is associated with a variety of extrahepatic syndromes, including central nervous system (CNS) abnormalities. However, it is unclear whether such cognitive abnormalities are a function of systemic disease, impaired hepatic function, or virus infection of the CNS. METHODS We measured levels of HCV RNA and expression of the viral entry receptor in brain tissue samples from 10 infected individuals (and 3 uninfected indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 46 publications
(57 reference statements)
6
155
0
5
Order By: Relevance
“…This major TJ protein that plays an important role in TJ integrity has a low expression in cerebrovascular endothelium. In agreement with other studies,30, 31 protein expression of CLDN1 in the intact control (NC) HBMECs was extremely low and almost undetectable either with immunofluorescence staining or Western blot. Similar to NC samples, in the OGD cells transfected with control oligonucleotides (CLDN1 distribution and expression was similar in OGD/IC and OGD/MC control samples), CLDN1 distribution was mostly cytoplasmic and the expression was weak (Figure 5A, OGD/IC panel).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This major TJ protein that plays an important role in TJ integrity has a low expression in cerebrovascular endothelium. In agreement with other studies,30, 31 protein expression of CLDN1 in the intact control (NC) HBMECs was extremely low and almost undetectable either with immunofluorescence staining or Western blot. Similar to NC samples, in the OGD cells transfected with control oligonucleotides (CLDN1 distribution and expression was similar in OGD/IC and OGD/MC control samples), CLDN1 distribution was mostly cytoplasmic and the expression was weak (Figure 5A, OGD/IC panel).…”
Section: Resultssupporting
confidence: 93%
“…While CLDN5 is highly expressed in the brain endothelium, CLDN1 expression in cerebral capillaries is low and was only confirmed to be present in human, rat, and sheep BBB 3, 30, 31. Regardless of the low expression, CLDN1 function in human brain capillaries is critical for the maintenance of the BBB integrity during neuroinflammation and brain tumor 29, 44.…”
Section: Discussionmentioning
confidence: 99%
“…These cell lines were the first extra-hepatic cells that sustain HCV infection without ectopic expression of cellular factor required for viral entry (Lindenbach 2010). HCV tropism for the brain is further supported by a recent study by Fletcher et al demon strating productive HCV infection of brain microvascular en dothelial cells (BMEC), a major component of the blood/brain bar rier (Fletcher, Wilson et al 2012). In this study, two independent de rived brain microvascular endothelial cell lines were described to ex press all HCV receptor molecules and could be infected with HCVpp and HCVcc.…”
Section: Permissive Host Cellsmentioning
confidence: 63%
“…35 What is more, SPECT studies have shown decreased binding capacity of a serotonin transporter in the mesencephalon and/or dopamine transporter in the striatum in 14 out of 20 examined patients independently of their PCR status. 34 Patients with disturbed monoamine transporter binding capacity achieved significantly worse results upon psychometric testing (especially with regard to mood and cognition) compared to the control group. Hence, the disturbances of monoaminergic neurotransmission may be an important factor of the CNS dysfunction in the course of HCV infection.…”
Section: Etiopathogenesis Of Cns Impairmentmentioning
confidence: 93%
“…That study suggests that HCV may disrupt the integrity of the blood/brain barrier in vivo as well. 34 The presence and replication of HCV has been found also in BMEC which indicates that the blood/brain barrier may be directly involved in HCV brain pathogenesis. 1,3 The secondary effects of a chronic inflammatory systemic process and the role of cytokines, which are presumably mediating the cognitive dysfunction, is an important part of the etiopathogenesis of the CNS pathology in the course of hepatitis C.…”
Section: Etiopathogenesis Of Cns Impairmentmentioning
confidence: 99%